PARENTS' PERCEPTIONS OF LEARNING ENGLISH FOR EARLY CHILDREN - Melinda Puspita Sari Jaya; Santa Idayana Sinaga; Bambang Purwanto, Muhammad (Universitas Sarjanawiyata Tamansiswa, 2023)
This scientific essay examines the value of English language educating young children. Along with a nation's progress, English education is essential. As a result, Students are exposed to English as an international language as early as possible, before they reach 12 years of age. Young children are when a child is in the age range of the ideal time for language learning is between the ages of two and seven. They have the capacity to acquire native-like speech. They remain in a pre-operational cognitive development state, meaning they do not comprehend abstract concepts; they only comprehend symbols and think pre-logically. As a result, teaching English to children needs the use of appropriate and effective methods and procedures, such as singing, music, and giving physical education priority. This approach is regarded as effective and appropriate for learning English in young children. Developing this method also requires the involvement of teachers and parents learning English as a second language